2017
DOI: 10.1017/s1468109917000081
|View full text |Cite
|
Sign up to set email alerts
|

Media Use, Democratic Values, and Political Participation: Empirical Evidence from Taiwan

Abstract: This paper extends understanding of the relationship between media use and attitudes toward democratic values. We employ the two-step estimation approach to examine the relationship between media use and attitudes toward democratic values as well as consequential association with political participation. The empirical results show that media use to obtain news information is positively related to attitudes toward democratic values. The findings also note that attitudes toward democratic values are positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Chang (2016, p. 259) argues that ‘the change in the range of available media may significantly alter people's perceptions about political parties, politicians, and public policies, and therefore change the existing political institutions and the pattern of people's political engagement’ and finds that internet use lowers normative support for duty‐based citizenship. In later work, examining media use and political participation in Taiwan, Chang (2017, p. 400) found that ‘media use plays a significant role in cultivating citizens' democratic citizenship’. As scholars acknowledge a ‘law of group polarization’ and identify an ‘echo chamber effect’ it is necessary to consider how reciprocal commitments to the CSC have changed (Sunstein 2001, 2002).…”
Section: The Social Contractmentioning
confidence: 99%
“…Chang (2016, p. 259) argues that ‘the change in the range of available media may significantly alter people's perceptions about political parties, politicians, and public policies, and therefore change the existing political institutions and the pattern of people's political engagement’ and finds that internet use lowers normative support for duty‐based citizenship. In later work, examining media use and political participation in Taiwan, Chang (2017, p. 400) found that ‘media use plays a significant role in cultivating citizens' democratic citizenship’. As scholars acknowledge a ‘law of group polarization’ and identify an ‘echo chamber effect’ it is necessary to consider how reciprocal commitments to the CSC have changed (Sunstein 2001, 2002).…”
Section: The Social Contractmentioning
confidence: 99%
“…During their free travel time, Taiwanese students encounter social life in Mainland China and discuss the trip with their peers. Therefore, peer groups and mass media may both play a role in political learning (Chang, 2017; Li and Feng, 2018; Quintelier et al, 2012).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…The value of integrity is achieved through the comparative quality of political information (Wolfsfeld et al, 2015), where political information positively impacts civic activity in society (Trenz, 2015), strengthens the practice of national democracy (Chang 2017), and belief in the political system (Valenzuela et al, 2009), where this value of trust refers to the integrity and efficiency of the leadership system, the efficiency and moral value of coping with political pressures, and prioritizing responsive actions to the people (Carlin, 2014).…”
Section: Analyse and Evaluate Political Information Sources In Social Mediamentioning
confidence: 99%